The use of bioelectrical impedance to detect excess visceral and subcutaneous fat - Fernandes, Romulo A.; Rosa, Clara S. C. [UNESP]; Buonani, Camila [UNESP]; de Oliveira, Arli R.; Freitas, Ismael F. [UNESP] (Sociedade Brasileira de Pediatria, 2007)
objective: To analyze bioelectrical impedance performance in detecting the presence of excess visceral fat and overweight/obesity in young Brazilians and how its values are related with them.Methods: Study sample consisted of 811 adolescents of both genders (11 to 17 years of age). Nutritional status was determined based on triceps skinfold thickness (TSF), relative body fat (bioelectrical impedance), and excess visceral fat as determined by waist circumference. Statistical analysis was performed using means, standard deviations, linear correlation, Student's t test, and ROC curve.Results: Bioelectrical impedance achieved good performance in identifying excess visceral fat associated with overweight/obesity in both genders, and was found to be more specific (male 92.4% and female 93.8%) than sensitive (male 86.1% and female 71.8%).Conclusion: Our findings support the use of bioelectrical impedance to identify the presence of excess visceral and subcutaneous fat in adolescents.